E-learning gamification and vocabulary acquisition in primary students - Arévalo Contreras, Karem Elizabeth (2024)
The aim of this research endeavor is to examine the impact of using gamified activities into the online classroom on the vocabulary development of second-grade scholars enrolled in the online track of the Zoila Online Master Educational Unit. By employing suitable data collection methodologies, it became feasible to discern and comprehend that students encounter challenges in effectively communicating in English, thereby restricting their capacity for educational interaction within the classroom setting. The inadequate mastery of the English vocabulary has had an impact on the engagement, participation, and motivation of the majority of students with regard to the tasks that the instructor has assigned for online learning. In order to address this problem, practical solutions are presented, as well as a teacher's guide, which is based on efficient, practical, and appropriate educational technology to facilitate a more enjoyable second language instruction.